The Ocak (Hearth) of Teslim Abdal in the Context of Tradition and Ritual Continuity (Journal of Alevism-Bektashism Studies, 2020)
This paper is a follow-up to our first paper on the historical process of forming an “ocak” (hearth) cult in the context of five different documents of the “secerename” and “icazetname” genres about the “ocak” (hearth) of Teslim Abdal, dated 1791-1792, December 5, 1792, May 11, 1817, May 1, 1842 and January/February 1885, located in the personal archives of the “dede” (spiritual leader) families, members of the “ocak”. Our paper includes a comprehensive analysis and evaluation of the findings about the “ocak” in question that we obtained from oral tradition based on fieldwork. In this context, the paper addresses the process of forming an independent “ocak” cult centred primarily around the personality of Teslim Abdal, who has the qualities of an Alevi poet and a spiritual leader. We obtained the information about the “ocak” of Teslim Abdal, which is continuation and have the characteristics of a branch of the “ocak” of Sheikh Ahmed Dede, primarily through interviews with the “dede” and aspirants of the ocak. These interviews, conducted with the “dede” and aspirants from the village of Shih Hasan (now known as Tabanbuku) of Baskil district, Elazig, who are now living in various locations of Malaty, Elazig, Antalya and Izmir, cover different periods of time from 2014 to 2020. As a result of comparing the information obtained through both the interviews with “dede” and aspirants and fieldwork in the village of Shih Hasan, with the documents from the personal archives of the “dedes”, we presented the process of forming of the “ocak” of Teslim Abdal as an independent “ocak”, the hierarchy of it and the geographical area where the “dede” and aspirant communities live. We also determined and evaluated the current state of the “ocak” and its ritual-centred continuity.